72 Angiopoietin-like 4, A Novel Mechnoresponse Protein Involved In Tendinopathy. (5th September 2014) - Mousavizadeh, Rouhollah; Duronio, Vincent; Behzad, Hayedeh; McCormack, Robert G; Scott, Alexander
Abstract : Introduction: Tendinopathy is often viewed as the result of failed or inadequate healing response in response to subclinical injury. 1 Previous authors have suggested there may be an association between pain and neurovascular changes resulting from a failed healing response in tendinopathy patients. 2, 3 Our previous study has shown that cyclic strain induces an array of angiogenic genes in human tendon cells which promote angiogenesis. 4 Our recent data introduced a new mechanoresponse protein named Angiopoietin-like 4 (ANGPTL4) which regulates angiogenesis. In this study we characterised the function of ANGPTL4 protein in tendon and its regulatory pathways in response to mechanical stimuli. Methods: The angiogenic activity of ANGPTL4 was determined with an endothelial cell tube-formation assay. Immunohistochemistry and gene expression analyses were conducted with mouse patellar tendons which were harvested after injection with ANGPTL4 protein or saline control. By using a Flexcell Tension System, isolated tendon cells from human hamstring tendons were exposed to cyclic tension. ANGPTL4 concentration and TGF-β activity in conditioned media were determined with ELISA and dual-luciferase reporter assays respectively. The following conditions were applied to evaluate the mechanisms regulating ANGPTL4 production: TGF-β protein and its receptor antagonist, hypoxia, and a HIF-1α stabiliser and/or inhibitor. Human cuff rotator tendon biopsies were examined by immunostaining with ANGPTL4, HIF-1α and CD-31 antibodies. Results: ANGPTL4 protein induces endothelial cell tube formation, and angiogenic markers in mouse patellar tendon. The protein also induces MMP3 expression in the mouse tendon (Figure 1 ). Our findings illustrate that cyclic strain induces expression and release of ANGPTL4 through increased activity of TGF-β and stabilising HIF-1α (Figure 2 ). The data from immunostaining of human rotator tendon tissue indicate a correlation between the expression of ANGPTL4, HIF-1α and endothelial cell marker which support the role of HIF-1α in induction of ANGPTL4 followed by angiogenesis (Figure 3 ). Discussion: This study has begun to unravel the potential role of ANGPTL4 protein in tendon. It seems that HIF-1α and TGF-β pathways modulate the expression and release of ANGPTL4 in response to cyclic loading. Therefore, these pathways might regulate neovascularization during overuse tendinopathy. Our future studies on animal models will examine the effects of ANGPTL4 during the course of tendon healing and injury. References: Dirks RC, Warden SJ. J Musculoskelet Neuronal Interact. 2011;11(2):141–149 Divani K, et al . Man Ther. 2010;15(5):463–468 Magnusson SP, et al . Nat Rev Rheumatol. 2010;6(5):262–268 Mousavizadeh R, et al . PLoS One 2014;9(5):e97356